CYBERSECURITY AND AI IN THE NEXT ERA OF BANKING EFFICIENCY IN UZBEKISTAN (2015–2024) (World Bulletin of Management and Law, 2026)
This research explores the impact of cybersecurity investment and artificial intelligence (AI) adoption on effectiveness, competitiveness and financial stability in commercial banks of Uzbekistan within digitalization process.
Keywords: Cybersecurity; Artificial Intelligence; Banking Efficiency; Panel Data; Panel-VAR; Digitalization; Return on Assets; Uzbekistan.